2021
DOI: 10.35188/unu-wider/2021/955-6
|View full text |Cite
|
Sign up to set email alerts
|

Can information campaigns reduce last mile payment delays in public works programme? Evidence from a field experiment in India

Abstract: Does information dissemination among beneficiaries of welfare programmes mitigate their implementation failures? We present experimental evidence in the context of a rural public works programme in India, where we assess the impact of an intervention that involves dissemination of publicly available micro-level data on last mile delays in payment and programme uptake, along with a set of intermediate outcomes. The findings point to a substantial reduction in last mile payment delays along with improvements in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The expansion of social welfare programs has increased the quality of life of the poor, and made them resilient to multiple, but it has also increased political disquiets around its form, focus, and scope. Political debates have 57 Das et al (2021), in an experimental study, show that providing personalized communications and community canvassing-disseminating publicly available information on the provisions of MGNREGS, workers listed, beneficiary wages, and date of receiptincreases the take-up of work and reduces payment delays through increased accountability of local implementing institutions. An experimental study in Indonesia also shows that once the beneficiary lists and their entitlements were made public (through loudspeaker announcements and listing on the wall in the village), it created greater private information to seek welfare benefits and reduced the incentive of the local elite to discriminate against a person or a group (Banerjee et al 2018).…”
Section: Welfare Expansion: Good Economics But Contentious Politicsmentioning
confidence: 99%
“…The expansion of social welfare programs has increased the quality of life of the poor, and made them resilient to multiple, but it has also increased political disquiets around its form, focus, and scope. Political debates have 57 Das et al (2021), in an experimental study, show that providing personalized communications and community canvassing-disseminating publicly available information on the provisions of MGNREGS, workers listed, beneficiary wages, and date of receiptincreases the take-up of work and reduces payment delays through increased accountability of local implementing institutions. An experimental study in Indonesia also shows that once the beneficiary lists and their entitlements were made public (through loudspeaker announcements and listing on the wall in the village), it created greater private information to seek welfare benefits and reduced the incentive of the local elite to discriminate against a person or a group (Banerjee et al 2018).…”
Section: Welfare Expansion: Good Economics But Contentious Politicsmentioning
confidence: 99%
“…timely release of wages and reducing the leakages in the process. Moreover, Das et al, (2021) found that personalised information of wage credit listing to beneficiaries' bank accounts, reduced last mile payment delays. Here GRS (Gram Rojgar Sevak) and Sarpanch can contribute to information dissemination of not only wage credit listing but also beneficiaries' rights for the better implementation of the programme.…”
Section: Budgetary Allocation and Managerial Aspectsmentioning
confidence: 99%